2016
DOI: 10.15252/embj.201695513
|View full text |Cite
|
Sign up to set email alerts
|

Replication fork passage drives asymmetric dynamics of a critical nucleoid‐associated protein in Caulobacter

Abstract: In bacteria, chromosome dynamics and gene expression are modulated by nucleoid-associated proteins (NAPs), but little is known about how NAP activity is coupled to cell cycle progression. Using genomic techniques, quantitative cell imaging, and mathematical modeling, our study in Caulobacter crescentus identifies a novel NAP (GapR) whose activity over the cell cycle is shaped by DNA replication. GapR activity is critical for cellular function, as loss of GapR causes severe, pleiotropic defects in growth, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 81 publications
6
67
0
Order By: Relevance
“…In the multicellular bacterium Streptomyces coelicolor, two HU-like proteins, HupA and HupS, are responsible for chromosome organization in the vegetative hyphae and during sporulation, respectively (19). Interestingly, the cell cycle regulation of Caulobacter crescentus is dependent on the recently described GapR protein (20), a novel NAP whose DNA-binding activity is regulated by the passage of the replication fork.…”
mentioning
confidence: 99%
“…In the multicellular bacterium Streptomyces coelicolor, two HU-like proteins, HupA and HupS, are responsible for chromosome organization in the vegetative hyphae and during sporulation, respectively (19). Interestingly, the cell cycle regulation of Caulobacter crescentus is dependent on the recently described GapR protein (20), a novel NAP whose DNA-binding activity is regulated by the passage of the replication fork.…”
mentioning
confidence: 99%
“…Remarkably, a classification of cells according to their size (Fig.3A) showed that the shortest (swarmer/G1) cells usually displayed no focus, that longer (stalked/early S-phase) cells displayed foci close to the cell pole, while even longer (early pre-divisional/late S-phase) cells displayed foci near mid-cell. A timelapse microscopy experiment following the cell cycle of newly born swarmer/G1 cells ( Fig.3B) confirmed that the sub-cellular localization of MutS was very similar to that of the replisome (22,23,31) (Fig.3C).…”
Section: Muts Co-localizes With the Replisome Throughout The S-phasementioning
confidence: 56%
“…Positively charged amino acid residues at the C-terminus are critical for the DNA-binding activity of GapR As shown above, GapR and H-NS share a second functionally similar region: Helix 2 of GapR (14) and a segment of the C-terminal DNA-binding domain of H-NS (27). To confirm that this region of GapR is critical for binding DNA, we first compared the truncated GapR1-52 and the full length GapR1-89 with respect to their ability to co-purify with and directly bind DNA in vitro.…”
Section: Gapr Oligomerization Is Curtailed Upon Disruption Of Secondamentioning
confidence: 90%
“…Structurally determined elements are shown as boxed regions for α-helices and boxed regions with arrowheads for β-sheets (shown in green for GapR and blue for H-NS). Green bars shown above the GapR sequence correspond to the previously reported coiled-coil and DNA-binding motifs(14). Blue bars shown below the E. coli H-NS sequence correspond to the coiled-coil motif, the dimerization sites 1 and 2, the flexible linker and the DNA-binding domain(24)(25)(26)(27)(28).…”
mentioning
confidence: 95%